Field emission scanning electron microscopy (FESEM): an easy way to characterize morphologies of P3HT:PCBM coated and printed solar cells. (17th July 2019) - Po, Riccardo; Corso, Gianni; Cominetti, Alessandra; Carbonera, Chiara; Bernardi, Andrea; Di Paola, Eleonora; Carati, Claudio; Bonoldi, Lucia
Abstract: Poly(3-hexylthiophene): [6, 6]-Phenyl C61 butyric acid methyl ester (P3HT:PCBM) films used in organic solar cells were deposited in similar conditions (polymer:fullerene ratio, solvent, film thickness) by different techniques: slot-die coating (30 °C and 60 °C), gravure printing and spin coating. Electrical and morphological characterization were performed. Field emission scanning electron microscopy (FESEM) evidenced morphological differences on the macro-scale in a very effective way. Energy filtered transmission electron microscopy was applied to investigate meso-scale and nano-scale as well. Image analysis on FESEM images ensured the quantification of morphological differences and the selection of an effective single descriptive parameter. The set up of a fast technique to characterize morphology and of a 'simple' parameter to describe it is the main result of this work. This method is therefore optimal to support roll-to-roll deposition processes.